Khamnigan Identity in the Cultural Space of the East Trans-Baikal Transboundedness - Dina B. Sundueva; Transbaikal State University, Chita, Russia (Гуманитарный вектор)
The article is devoted to the phenomenon of cultural identity of the Khamnigan ethnic group, which is native to the cultural space of the East Trans-Baikal cross-border, unique in its ethnic and cultural diversity of the region. The cultural trinity of the border territories of Russia, Mongolia and China is ensured by cultural diffusion accompanied by strong assimilation processes. The trajectory of cross-border interaction development is characterized by cross-border asymmetries of social, demographic and cultural indicators. In this work, based on the specifics of the functioning of the Khamnigan language in the context of transboundary integration, as well as the speech material produced by its carriers, the types of Khamnigan identity are described: capsule, consolidation, diffuse, and pseudomorphic. The type of cultural identity, being the integral quality of all aggregate phenomena, determines a certain state of a small ethnic group in the assimilation processes of cross-border in their dynamics. A certain type of cultural identity is achieved by the presence in cultural reality of a cross-border qualitative characteristic of the state of identification traits in its structure. It has been established that the reason for the development of different types of Khamnigan identity in a cross-border region is the dispersed residence of members of this small ethnic group in the border territories of Russia, Mongolia and China and the policies towards small ethnic groups. The change of the barrier function of the border in the cultural space of the East Transbaikal cross-border at various stages of the joint history of the border territories significantly affected the nature of assimilation processes among members of the Khamnigan ethnic group. Research results can show their relevance for educational programs and to preserve the unique cultural heritage of Transbaikal.